Introducing Semantic Kernel: Building AI-Based Apps. - Maeda, John; Schillace, Sam (linkedin.com, 2023)
Get an overview of Semantic Kernel (SK), the latest addition to the Microsoft AI ecosystem that leverages LLMs and AI models to revolutionize software development.